Composite process and device for lithium battery ultra-thin diaphragm
Patent Information
- Application Number
- CN202611350029.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-30
AI Technical Summary
1.热稳定性与安全存在固有缺陷,复合层会在热压时会软化变形、孔隙率下降、透气性变差,可能导致加速热失控
1、通过半湿润态冷压复合工艺,陶瓷浆料中残余的水分和粘结剂在冷压过程中充当了原位粘合介质,既避免了热压工艺中因高温导致的涂层孔隙塌缩和透气性下降问题,又充分利用了陶瓷涂层自身的粘接特性实现两层薄膜的牢固复合,从而在保持隔膜良好孔隙率和透气性的同时,增强了复合隔膜的整体机械强度和抗穿刺能力,且冷压工艺无需加热能耗,降低了生产成本和工艺控制难度。
Smart Images

Figure CN123018344A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of ultra-thin lithium-ion battery separators, and particularly to a composite process and apparatus for ultra-thin lithium-ion battery separators. Background Technology
[0002] The ultra-thin lithium battery separator composite coating equipment is a high-precision coating and composite equipment that uniformly, stably, and without defects coats organic ceramic coating slurry onto a high-speed running 3.5μm ultra-thin separator. Then, by controlling the humidity of the slurry on the membrane surface, a 7-9μm ultra-thin separator is produced through cold rolling.
[0003] The lithium-ion battery separator is a microporous membrane located between the positive and negative electrodes. Its core function is to prevent short circuits between the two electrodes while allowing lithium ions to pass freely. With the increasing demands for battery energy density and power density from new energy vehicles and high-end consumer electronics, ultra-thinning and high-performance have become key directions in separator development. When single polyolefin (PE / PP) separators reach ultra-thinness (e.g., <12μm, or even 7μm), their mechanical properties, thermal stability, and safety significantly decrease. Therefore, composite processes have emerged, combining the advantages of different materials to prepare composite separators that possess ultra-thinness, high strength, high heat resistance, and excellent electrolyte wettability.
[0004] The main purpose of using composite processes is: 1. Enhance safety: Inorganic ceramic coatings can effectively inhibit the shrinkage of the diaphragm at high temperatures, and the inorganic coating can act as a thermal barrier to prevent thermal runaway.
[0005] 2. Lightweight and thin separator provides higher energy density for the battery.
[0006] 3. Green and sustainable, water-based inorganic coating cold rolling composite process reduces energy consumption and the use of organic solvents.
[0007] Existing diaphragm lamination processes involve coating a functional slurry with a specific formulation onto a diaphragm substrate, drying it to form a functional coating, then hot-pressing a functional porous membrane onto the functional coating, and finally performing post-treatment via UV crosslinking and curing. During the crosslinking process, the double bonds in the heat-sensitive and pressure-sensitive functional resins break, generating free radicals, which then undergo a polymerization reaction to form an insoluble and infusible cured network structure. This significantly improves the thermal stability and adhesion of the functional coating, effectively enhancing the bond strength between the diaphragm substrate and the functional coating, as well as between the functional coating and the functional porous membrane. While imparting excellent heat resistance or adhesive properties to the diaphragm by adding a functional coating, the functional slurry does not contain any adhesive that can be dried to form a film. Both the heat-sensitive and pressure-sensitive functional resins are coated on the diaphragm surface in granular form, with numerous gaps between the particles, which are then bonded and laminated through subsequent hot pressing.
[0008] However, existing technologies have the following problems: 1. There are inherent defects in thermal stability and safety. The composite layer will soften and deform, decrease porosity and reduce air permeability during hot pressing, which may lead to accelerated thermal runaway.
[0009] 2. Thermal lamination is prone to creep, which can lead to uneven bonding between membranes and an incomplete overall structure of the laminated membrane, thus reducing its puncture resistance.
[0010] 3. Poor electrochemical stability and compatibility.
[0011] 4. Thermosensitive resins are sensitive to temperature, have complex process control, and have a low yield.
[0012] 5. Thermal bonding processes are difficult to firmly bond high proportions of ceramic slurry, resulting in limited functionality and low design flexibility.
[0013] 6. It is not conducive to providing battery energy density. Summary of the Invention
[0014] The purpose of this invention is to provide a composite process and apparatus for ultra-thin lithium battery separators, which maintains and optimizes porosity and air permeability, enhances mechanical strength and puncture resistance, and simplifies the process and reduces costs.
[0015] To solve the above-mentioned technical problems, the present invention provides a composite process for an ultra-thin lithium battery separator, comprising the following steps: S100, coating a ceramic slurry on the composite surface of a separator substrate, the ceramic slurry comprising 100 parts of alumina, 10-14 parts of binder, 0.8-1.6 parts of thickener, 0.6-0.8 parts of dispersant, and deionized water with a solids content of 32%-40%; S200, drying the coated separator substrate to remove 40%-60% of the moisture in the ceramic slurry; S300, pressing a functional porous film onto the composite surface of the separator substrate using a cold pressing composite method, so that the two are pressed together to form a composite separator.
[0016] In one embodiment, the binder is an aqueous acrylate emulsion; the thickener is sodium carboxymethyl cellulose (CMC-Na); and the dispersant is ammonium polyacrylate.
[0017] In one embodiment, in S200, the drying temperature of the diaphragm substrate is 50-60°C.
[0018] In one embodiment, in S300, the composite diaphragm is dried again before being wound up.
[0019] In one embodiment, in S300, the composite pressure of cold pressing is controlled at 0.25-0.4 bar.
[0020] In one embodiment, the conveying rate is controlled at 80-130 m / min when conveying the diaphragm substrate, the functional porous film, and the composite diaphragm.
[0021] To address the aforementioned technical problems, this invention also provides a composite apparatus for ultra-thin lithium-ion battery separators, used to perform the aforementioned composite process, comprising a first unwinding unit, a second unwinding unit, a coating unit, a dehydration oven, a cold-pressing composite unit, and a winding unit; the first unwinding unit outputs a separator substrate to the coating unit; the coating unit applies a ceramic slurry to the composite surface of the separator substrate; the dehydration oven receives the coated separator substrate and dries it; the second unwinding unit outputs a functional porous film to the composite unit; and the cold-pressing composite unit cold-presses the separator substrate and the functional porous film together to form a composite separator.
[0022] In one embodiment, the cold-pressing composite unit includes a composite steel roller and a composite rubber roller arranged separately from each other; the composite steel roller is used to roll against the diaphragm substrate; the composite rubber roller is used to roll against the functional porous film; the composite steel roller and the composite rubber roller are both used to press together to form the composite diaphragm.
[0023] In one embodiment, the composite steel roller and the composite rubber roller are designed to move toward each other or move apart.
[0024] In one embodiment, a re-drying oven is provided between the cold-pressing composite unit and the winding unit, and the re-drying oven is used to dry the composite diaphragm.
[0025] The beneficial effects of this invention are as follows: 1. Through the semi-wet state cold pressing composite process, the residual moisture and binder in the ceramic slurry act as an in-situ bonding medium during the cold pressing process. This avoids the problems of coating pore collapse and reduced air permeability caused by high temperature in the hot pressing process, and makes full use of the adhesive properties of the ceramic coating itself to achieve a firm composite of the two films. Thus, while maintaining the good porosity and air permeability of the diaphragm, it enhances the overall mechanical strength and puncture resistance of the composite diaphragm. Moreover, the cold pressing process does not require heating energy consumption, reducing production costs and process control difficulty.
[0026] 2. By selecting the binder, thickener and dispersant in the above-mentioned water-based system, the resulting ceramic slurry uses water as the dispersion medium and does not contain organic solvents such as NMP, which has the advantages of being environmentally friendly and cost-effective. At the same time, the synergistic effect of each component gives the slurry good coating leveling and storage stability, and it can be uniformly coated on the surface of the diaphragm substrate, providing a suitable coating state for subsequent semi-wet cold pressing lamination.
[0027] 3. By setting the drying temperature to 50-60℃, the membrane substrate is heated gently during the drying and dehydration process, which effectively prevents problems such as shrinkage, curling or uneven thickness caused by overheating. This ensures the flatness and thickness consistency of the coating surface, which helps to improve the dimensional accuracy and appearance quality of the finished composite membrane. At the same time, the lower drying temperature also reduces heat consumption and equipment operating load.
[0028] 4. By drying the composite separator again before winding, residual moisture on the membrane surface is effectively eliminated, preventing membrane layer adhesion, wrinkles, or local adhesion defects caused by residual moisture after winding. This ensures that the composite separator is neatly wound and the layers separate smoothly, which is conducive to the smooth implementation of subsequent slitting, storage, and battery assembly processes, and further improves the product yield and storage stability.
[0029] 5. By controlling the cold-pressing composite pressure at 0.25-0.4 bar, a good bonding force is ensured between the membrane substrate and the functional porous film, while avoiding the problem of decreased porosity and reduced air permeability caused by excessive compaction of the ceramic coating due to excessive pressure. This effectively maintains the integrity of the porous structure inside the membrane while ensuring the composite strength, which is conducive to ensuring the smooth conduction of lithium ions in the membrane and the stable performance of the battery.
[0030] 6. By controlling the conveying rate at 80-130m / min, high-speed continuous production of the diaphragm preparation process is achieved. While maintaining the process effect of each step, the output efficiency per unit time is significantly improved. At the same time, stable high-speed conveying helps to reduce tension fluctuations and deviations of the membrane surface during operation, ensuring the uniformity of coating thickness and the alignment accuracy of the composite position. Thus, while improving production efficiency, the consistency of product quality is also taken into account.
[0031] 7. Through the coordinated operation of the various units of the above-mentioned device, continuous and automated production of diaphragm substrate coating, dehydration, cold pressing lamination and winding is realized. The sequential coordination of the dehydration oven and the cold pressing lamination unit ensures that the ceramic slurry remains in a suitable semi-wet state for bonding after pre-drying, providing in-situ bonding medium conditions for cold pressing lamination. Thus, the effective bonding of the two-layer film can be achieved without the need for hot pressing heating, simplifying the equipment structure and temperature control investment, and reducing production energy consumption and equipment manufacturing costs.
[0032] 8. By adopting a combined structure of composite steel rollers and composite rubber rollers, the steel rollers provide rigid support to keep the diaphragm substrate flat and stable during the pressing process, while the rubber rollers use their elastic deformation to apply uniform and gentle pressure to the functional porous membrane, so that the two can achieve good bonding under cold pressing conditions. At the same time, the elastic buffering effect of the rubber rollers can effectively avoid membrane surface damage or coating cracking caused by rigid extrusion, ensuring the interface bonding quality and appearance integrity of the composite diaphragm.
[0033] 9. By setting up a structure where the composite steel roller and the composite rubber roller can move towards or away from each other, the pre-production film threading and belt guiding operation is greatly simplified, reducing the difficulty of operation for operators and the downtime for auxiliary work; at the same time, during the production process, the pressing gap and composite pressure between the two rollers can be flexibly adjusted according to process requirements, and it can adapt to the composite requirements of diaphragm substrates and functional porous films of different thicknesses without changing equipment parts, thus improving the equipment's compatibility with different product specifications and production flexibility.
[0034] 10. By setting up a secondary drying oven between the cold-pressing lamination unit and the winding unit, the composite diaphragm that has just completed cold-pressing lamination can be dried in a timely and sufficient manner. This ensures that the composite diaphragm is completely free of residual moisture before winding, thereby avoiding problems such as adhesion between film layers, local adhesion defects, or wrinkling of the film surface after winding due to residual moisture on the film surface. This ensures the neatness of winding and the smoothness of slitting, and at the same time, it is conducive to the stable curing of the internal structure of the diaphragm, improving the product's storage stability and the reliability of subsequent use. Attached Figure Description
[0035] To more clearly illustrate the technical solution of the present invention, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0036] Figure 1 This is a structural schematic diagram provided in an embodiment of the present invention.
[0037] The attached figures are labeled as follows: 100. First unwinding unit; 200. Second unwinding unit; 300. Coating unit; 400. Dehydration drying oven; 500, Cold-pressed composite unit; 510, Composite steel roller; 520, Composite rubber roller; 600. Rewinding unit; 710. Membrane substrate; 720. Functional porous membrane; 730. Composite membrane; 800, Re-drying Oven. Detailed Implementation
[0038] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0039] The separator in a lithium-ion battery is located between the positive and negative electrodes, preventing short circuits and ensuring lithium-ion conduction. With increasing energy density requirements in new energy and consumer electronics, separators are trending towards ultra-thinness (≤12μm, even 7μm). However, the mechanical properties, thermal stability, and safety of single-polyolefin (PE / PP) separators significantly decrease in their ultra-thin state. Therefore, composite processes have been introduced to combine the advantages of different materials to prepare composite separators that possess ultra-thinness, high strength, high heat resistance, and good wettability, thereby improving safety, reducing weight, and supporting green manufacturing.
[0040] Existing composite processes typically involve coating functional slurries, drying, and then hot-pressing them to form functional porous films, followed by UV curing. However, this process has several drawbacks: hot pressing can easily lead to coating softening and deformation, decreased porosity, and reduced air permeability, increasing the risk of thermal runaway; uneven thermal bonding can cause creep, affecting the integrity of the membrane structure and its puncture resistance; furthermore, it suffers from poor electrochemical compatibility, complex process control, low yield, and difficulty in achieving a high proportion of ceramic coatings, thus limiting the improvement of membrane performance and further optimization of battery energy density.
[0041] To address the above problems, this invention provides a composite process for ultrathin lithium battery separators, comprising the following steps: S100 involves coating a ceramic slurry onto the composite surface of a diaphragm substrate. The ceramic slurry comprises 100 parts alumina, 10-14 parts binder, 0.8-1.6 parts thickener, 0.6-0.8 parts dispersant, and deionized water with a solids content of 32%-40%. S200 involves drying and dehydrating the coated diaphragm substrate to remove 40%-60% of the moisture from the ceramic slurry, creating a semi-wet state on the membrane surface, and then removing most of the coating moisture from the membrane surface. S300 uses a cold-pressing composite method to press a functional porous film onto the composite surface of a diaphragm substrate, so that the two are pressed together to form a composite diaphragm.
[0042] In the above process, step S200 removes 40%-60% of the moisture from the ceramic slurry by drying, creating a semi-wet state on the membrane surface. At this point, the alumina particles, binder, thickener, and dispersant in the ceramic coating still maintain a certain degree of fluidity and wettability under the influence of residual moisture. This prevents the coating from flowing or becoming uneven in thickness due to excessive moisture, and also prevents the particles from lacking an adhesive medium due to over-drying. Subsequently, in step S300, a cold-pressing composite method is used to directly press the functional porous membrane onto the surface of the semi-wet ceramic coating. Utilizing the residual moisture in the coating and the wetting and bonding properties of the binder, an effective bond between the diaphragm substrate and the functional porous membrane is achieved at room temperature.
[0043] Through the aforementioned semi-wet cold-pressing composite process, the residual moisture and binder in the ceramic slurry act as an in-situ bonding medium during the cold pressing process. This avoids the problems of coating pore collapse and reduced air permeability caused by high temperature in the hot pressing process, and makes full use of the adhesive properties of the ceramic coating itself to achieve a firm composite of the two films. Thus, while maintaining the good porosity and air permeability of the diaphragm, it enhances the overall mechanical strength and puncture resistance of the composite diaphragm. Furthermore, the cold pressing process does not require heating energy consumption, simplifies the temperature control process, and reduces production costs and process control difficulty.
[0044] To verify the actual situation of the present invention, multiple tests were conducted, and the test results are as follows: film thickness μm 3.5 3.5 4 4 Coating thickness μm 1 2 1 2 Product thickness (μm) 8.5-9.5 9.5-11.5 9.5-10.5 9.5-12.5 Breathability rating S / 100ml 230-270 200-240 160-200 190-230 Porosity % 37-41 33-37 38-42 34-38 Peel strength (180-degree dry peel) N / m 20-25 26-33 22-30 27-34 Heat shrinkage rate (%MD / TD) at 160℃ for 0.5 hours 1.9 / 1.3 1.9 / 1.1 2 / 1.2 1.8 / 1 Internal resistance Ω 35-40 45-54 30-35 43-50 Capacity retention % (0.5C) 96 93 95 92 As can be seen from the table above, the present invention also has at least the following beneficial effects: 1. The heat resistance and safety are significantly better than ordinary PE single-layer membranes. The closed-cell temperature of the double-layer PP matrix of the composite membrane is above 160℃, and the thermal shrinkage is very small at 105℃. Under the condition of high-rate continuous discharge and heat generation, the composite membrane is not prone to large-area shrinkage and short circuit, and has a higher safety redundancy for 3C fast charging and continuous high-current discharge.
[0045] 2. Water-based slurries have significant advantages in cost and environmental protection. Ceramic slurries do not use NMP organic solvents, resulting in lower raw material costs and lower investment in workshop explosion-proof measures. Alumina water-based coating electrolytes have good wettability and strong liquid retention capacity, which helps to reduce interfacial polarization.
[0046] 3. The cold composite double-layer structure of the composite diaphragm itself has better puncture and tear resistance, is suitable for high-speed winding, and has a higher upper limit for process yield.
[0047] 4. The preparation method of the present invention uses ceramic slurry itself as a binder, which can improve the safety and thermal stability of the diaphragm, maintain and optimize porosity and air permeability, enhance mechanical strength and puncture resistance, and simplify the process and reduce costs.
[0048] Preferably, in this embodiment, the binder is an aqueous acrylic emulsion; the thickener is sodium carboxymethyl cellulose (CMC-Na); and the dispersant is ammonium polyacrylate.
[0049] Preferably, in this embodiment, the drying temperature of the diaphragm substrate is set to 50-60°C in S200.
[0050] In step S200, controlling the drying temperature within a relatively mild range of 50-60℃ ensures that the membrane substrate maintains dimensional stability during heating, preventing thermal shrinkage or deformation of the polyolefin substrate due to excessively high temperatures. Simultaneously, this temperature condition is sufficient to drive the continuous evaporation of moisture from the ceramic slurry, reducing the water content to a predetermined removal rate of 40%-60%, allowing the membrane surface to smoothly transition to a semi-wet state and providing a suitable bonding humidity environment for subsequent cold-pressing lamination.
[0051] By setting the drying temperature to 50-60℃, the membrane substrate is heated gently during the drying and dehydration process, which can effectively prevent problems such as shrinkage, curling or uneven thickness caused by overheating. This ensures the flatness and thickness consistency of the coating surface, which helps to improve the dimensional accuracy and appearance quality of the finished composite membrane. At the same time, the lower drying temperature also reduces heat consumption and equipment operating load, which helps to save production energy costs.
[0052] Preferably, in this embodiment, the composite diaphragm is dried again in step S300 before being wound up.
[0053] After cold pressing lamination in step S300, the resulting composite separator still contains a small amount of moisture from the ceramic slurry. If this residual moisture is not removed before winding, it may cause the membrane layers to stick together or become unevenly bonded under winding pressure, affecting subsequent slitting and performance. Therefore, the composite separator is dried again before winding to allow the residual moisture on the membrane surface and inside the coating to evaporate fully, ensuring that the composite separator is dry when winding.
[0054] By drying the composite separator again before winding, residual moisture on the membrane surface can be effectively eliminated, preventing membrane layer adhesion, wrinkles, or local adhesion defects caused by residual moisture after winding. This ensures that the composite separator is neatly wound and the layers separate smoothly, which is conducive to the smooth implementation of subsequent slitting, storage, and battery assembly processes, and further improves the product yield and storage stability.
[0055] Preferably, in this embodiment, the composite pressure of cold pressing is controlled at 0.25-0.4 bar in S300.
[0056] During the cold-pressing lamination process in step S300, the lamination pressure is controlled within a relatively low range of 0.25-0.4 bar, allowing the lamination steel roller and lamination rubber roller to apply appropriate pressure to the diaphragm substrate and the functional porous membrane. Under this pressure condition, the semi-wet ceramic coating, acting as an adhesive medium, is uniformly compacted, ensuring sufficient interfacial contact and bonding strength between the diaphragm substrate and the functional porous membrane, while preventing excessive compression of the coating structure or particle breakage due to excessive pressure.
[0057] By controlling the cold-pressing composite pressure at 0.25-0.4 bar, it is possible to ensure good bonding between the separator substrate and the functional porous film, while avoiding the problems of decreased porosity and reduced air permeability caused by excessive compaction of the ceramic coating due to excessive pressure. This effectively maintains the integrity of the porous structure inside the separator while ensuring the composite strength, which is conducive to ensuring smooth conduction of lithium ions in the separator and stable performance of the battery.
[0058] Preferably, in this embodiment, the conveying rate is controlled at 80-130 m / min when conveying the diaphragm substrate, the functional porous film, and the composite diaphragm.
[0059] When conveying the diaphragm substrate, functional porous membrane, and composite diaphragm in the entire production line, the conveying speed is controlled within a high-speed range of 80-130 m / min. This ensures a continuous and stable operating rhythm as the diaphragm substrate sequentially passes through coating, drying and dehydration, cold pressing lamination, and re-drying processes. At this conveying speed, the residence time of the diaphragm substrate between each process unit is well matched with the processing time required for each process step, thereby ensuring that the drying and dehydration effect, the quality of cold pressing lamination, and the adequacy of re-drying are all effectively guaranteed.
[0060] By controlling the conveying rate at 80-130 m / min, high-speed continuous production of the diaphragm preparation process was achieved. While maintaining the process effect of each step, the output efficiency per unit time was significantly improved. At the same time, stable high-speed conveying helps to reduce tension fluctuations and deviations of the membrane surface during operation, ensuring the uniformity of coating thickness and the alignment accuracy of the composite position. Thus, while improving production efficiency, the consistency of product quality is also taken into account.
[0061] To address the aforementioned problems, the present invention also provides a composite device for ultra-thin lithium-ion battery separators, used to perform the aforementioned composite process, such as... Figure 1As shown, this embodiment includes a first unwinding unit 100, a second unwinding unit 200, a coating unit 300, a dehydration oven 400, a cold-pressing composite unit 500, and a take-up unit 600. The first unwinding unit 100 outputs the diaphragm substrate 710 to the coating unit 300. The coating unit 300 applies ceramic slurry to the composite surface of the diaphragm substrate 710. The dehydration oven 400 receives the coated diaphragm substrate 710 and dries it. The second unwinding unit 200 outputs the functional porous film 720 to the composite unit. The cold-pressing composite unit 500 cold-presses the diaphragm substrate 710 and the functional porous film 720 together to form a composite diaphragm 730.
[0062] During operation of the composite device, the first unwinding unit 100 continuously outputs the diaphragm substrate 710 and sends it to the coating unit 300. The coating unit 300 uniformly coats the ceramic slurry onto the composite surface of the diaphragm substrate 710. The coated diaphragm substrate 710 then enters the dehydration oven 400, where 40%-60% of the moisture in the ceramic slurry is removed at a drying temperature of 50-60°C, making the membrane surface semi-wet. Subsequently, the second unwinding unit 200 synchronously outputs the functional porous membrane 720 to the cold pressing composite unit 500, where it is cold-pressed with the semi-wet diaphragm substrate 710 from the dehydration oven 400 at a composite pressure of 0.25-0.4 bar to form a composite diaphragm 730. Finally, the composite diaphragm 730 is wound up by the winding unit 600.
[0063] Through the coordinated operation of the various units of the above-mentioned device, continuous and automated production of diaphragm substrate 710 coating, dehydration, cold pressing lamination and winding is realized. The sequential coordination of the dehydration oven 400 and the cold pressing lamination unit 500 ensures that the ceramic slurry remains in a suitable semi-wet state for bonding after pre-drying, providing in-situ bonding medium conditions for cold pressing lamination. Thus, the effective bonding of the two-layer film can be achieved without the need for hot pressing heating, simplifying the equipment structure and temperature control investment, and reducing production energy consumption and equipment manufacturing costs.
[0064] like Figure 1 As shown, this embodiment provides a cold-pressed composite unit 500 including a composite steel roller 510 and a composite rubber roller 520 arranged separately from each other; the composite steel roller 510 is used to roll against the diaphragm substrate 710; the composite rubber roller 520 is used to roll against the functional porous membrane 720; the composite steel roller 510 and the composite rubber roller 520 are both used to press together to form a composite diaphragm 730.
[0065] During cold pressing, the diaphragm substrate 710 enters the space between the composite steel roller 510 and the composite rubber roller 520 after passing through the dehydration oven 400. The composite steel roller 510 rolls against the ceramic coating side of the diaphragm substrate 710, and the composite rubber roller 520 rolls against the functional porous membrane 720 side. As they rotate in opposite directions, they pull the diaphragm substrate 710 and the functional porous membrane 720 through the pressing gap between the two rollers. Under the action of the rollers, the semi-wet ceramic coating is compacted as an adhesive medium, so that the functional porous membrane 720 is tightly attached to the composite surface of the diaphragm substrate 710, thereby continuously outputting the composite diaphragm 730.
[0066] By employing a combined structure of composite steel roller 510 and composite rubber roller 520, the steel roller provides rigid support to keep the diaphragm substrate 710 flat and stable during the pressing process, while the rubber roller uses its elastic deformation to apply uniform and gentle pressure to the functional porous film 720, so that the two can achieve good bonding under cold pressing conditions. At the same time, the elastic buffering effect of the rubber roller can effectively avoid membrane surface damage or coating cracking caused by rigid extrusion, ensuring the interface bonding quality and appearance integrity of the composite diaphragm 730.
[0067] Preferably, in this embodiment, the composite steel roller 510 and the composite rubber roller 520 are configured to move towards each other or away from each other.
[0068] The composite steel roller 510 and the composite rubber roller 520 can move towards each other or away from each other. During film threading or maintenance shutdown, the composite steel roller 510 and the composite rubber roller 520 are moved away from each other by the drive mechanism, so that a gap is created between the two rollers, which facilitates the diaphragm substrate 710 and the functional porous film 720 to pass through the channel between the two rollers to complete the film threading operation. During production, the composite steel roller 510 and the composite rubber roller 520 are moved towards each other to the set pressing position, so that the two rollers apply the required composite pressure to the diaphragm substrate 710 and the functional porous film 720 to achieve continuous cold pressing composite.
[0069] By setting up a structure that allows the composite steel roller 510 and the composite rubber roller 520 to move towards or away from each other, the pre-production film threading and belt guiding operation is greatly simplified, reducing the difficulty of operation for operators and the downtime for auxiliary work. At the same time, during the production process, the pressing gap and composite pressure between the two rollers can be flexibly adjusted according to process requirements. It can adapt to the composite requirements of membrane substrates 710 and functional porous films 720 with different thicknesses without changing equipment parts, thus improving the equipment's compatibility with different product specifications and production flexibility.
[0070] like Figure 1 As shown, in this embodiment, a re-drying oven 800 is provided between the cold pressing composite unit 500 and the winding unit 600. The re-drying oven 800 is used to dry the composite diaphragm 730.
[0071] After the diaphragm substrate 710 and the functional porous film 720 are pressed together by the cold pressing composite unit 500 to form a composite diaphragm 730, the composite diaphragm 730 immediately enters the re-drying oven 800. Inside the re-drying oven 800, the composite diaphragm 730 is further heated and dried so that the composite diaphragm 730 reaches a completely dry state before being wound up. After the dried composite diaphragm 730 is output from the re-drying oven 800, it is wound up by the winding unit 600.
[0072] By setting up a secondary drying oven 800 between the cold-pressing lamination unit 500 and the winding unit 600, the composite diaphragm 730 that has just completed cold-pressing lamination can be dried in a timely and sufficient manner. This ensures that the composite diaphragm 730 is completely free of residual moisture before winding, thereby avoiding problems such as adhesion between film layers, local adhesion defects, or wrinkling of the film surface caused by residual moisture on the film surface after winding. This ensures the neatness of winding and the smoothness of slitting, and at the same time, it is conducive to the stable curing of the internal structure of the diaphragm, improving the product's storage stability and the reliability of subsequent use.
[0073] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A composite process for an ultra-thin lithium battery separator, characterized in that... Includes the following steps, S100, a ceramic slurry is coated on the composite surface of the diaphragm substrate, the ceramic slurry comprising 100 parts alumina, 10-14 parts binder, 0.8-1.6 parts thickener, 0.6-0.8 parts dispersant, and deionized water with a solids content of 32%-40%; S200, the coated diaphragm substrate is dried to remove water, thereby removing 40%-60% of the moisture from the ceramic slurry; S300 employs a cold-pressing composite method, pressing a functional porous film onto the composite surface of the diaphragm substrate to form a composite diaphragm.
2. The composite process according to claim 1, characterized in that, The adhesive is an aqueous acrylic emulsion; The thickener is sodium carboxymethyl cellulose; The dispersant is ammonium polyacrylate.
3. The composite process according to claim 1, characterized in that, In S200, the drying temperature of the diaphragm substrate is 50-60°C.
4. The composite process according to claim 1, characterized in that, In S300, the composite diaphragm is dried again before being wound up.
5. The composite process according to claim 1, characterized in that, In S300, the composite pressure for cold pressing is controlled at 0.25-0.4 bar.
6. The composite process according to claim 1, characterized in that, When conveying the diaphragm substrate, the functional porous film, and the composite diaphragm, the conveying rate is controlled at 80-130 m / min.
7. A composite device for lithium battery ultrathin separators, used to perform the composite process according to any one of claims 1 to 6, characterized in that, It includes a first unwinding unit, a second unwinding unit, a coating unit, a dehydration oven, a cold pressing and laminating unit, and a rewinding unit; The first unwinding unit is used to output the diaphragm substrate to the coating unit; The coating unit is used to coat the ceramic slurry onto the composite surface of the diaphragm substrate; The dehydration oven unit is used to receive the coated diaphragm substrate and perform a drying operation on it; The second unwinding unit is used to output the functional porous film to the composite unit; The cold-pressing composite unit is used to cold-press the diaphragm substrate and the functional porous film together to form a composite diaphragm.
8. The composite device according to claim 7, characterized in that, The cold-pressing composite unit includes composite steel rollers and composite rubber rollers arranged separately from each other; The composite steel roller is used to roll and abut against the diaphragm substrate; The composite rubber roller is used to roll and abut against the functional porous film. The composite steel roller and the composite rubber roller are used to press together to form the composite diaphragm.
9. The composite device according to claim 8, characterized in that, The composite steel roller and the composite rubber roller are designed to move towards each other or move apart.
10. The composite device according to claim 7, characterized in that, A re-drying oven is provided between the cold-pressing composite unit and the winding unit, and the re-drying oven is used to dry the composite diaphragm.
